A numerical investigation on the performance of composite anchors for CFRP tendons. (1st June 2016) - Cai, Dong-sheng; Xu, Zhao-hui; Yin, Jie; Liu, Rong-gui; Liang, Ge
Highlights: We established a pertinent numerical ANSYS model to investigate the performance of composite anchor. We evaluated the three key parameters for composite anchor system with respect to the internal radial stress based on the numerical model. We recommended an optimized parameter combination for composite anchor system design. Abstract: This paper presents a numerical survey on the composite anchoring performance for Carbon Fiber Reinforced Polymer (CFRP) tendon. A numerical ANSYS model was established based on a previous experimental test data and analysis on a given configuration of composite anchor as well as some reasonable assumptions on the interface contact, adhesion and bond-slip. Surface to surface contact element was set to simulate the interfaces among anchor ring, wedge clamping and sleeve. Nonlinear spring elements to simulate the bond slip between CFRP tendon and adhesive. Simulation results agree well with the test results which indicate that the model has a good feasibility and can be used to simulate the anchoring performance. The internal radial stress on sleeve due to wedge clamping is an important index to reflect the anchor performance. Three key parameters ( θ 2, Δ θ and F P ) including wedge clamping angle ( θ 2 ), angle difference ( Δ θ = θ 1 - θ 2 ) between anchor ring angle ( θ 1 ) and wedge clamping angle ( θ 2 ), as well as pre-tightening force ( F P ) for composite anchor system were therefore evaluated with respect to the internal radial stress based on the numerical model. Results show that both θ 2 and Δ θ are sensitive to the anchoring performance and insensitive with F P . An optimized parameter combination is recommended in practice for composite anchor system design with θ 2 = 6 °, Δ θ = 0.1 °, and with no pre-tightening force.